Financial stability: New, detailed datasets allow for innovation of stress tests - Justus Inhoffen; Iman van Lelyveld (DIW Weekly Report, 2020)
The 2008-2010 crisis has shown that authorities were missing crucial information necessary to identify risks to the financial system in an accurate and timely manner. To be prepared for future crises, a range of legislation in Europe and beyond was passed. The scope and depth of information being reported from across the financial system, including previously disregarded segments, have thus significantly increased. With a focus on stress tests, we examine how granular datasets increase the transparency of the financial system's interconnectedness as well as the health of its market participants. We show that risks propagate primarily in the asset class of equities and via strong domestic links. This makes the data collection necessary to identify previously opaque risk drivers and derive effective policy recommendations despite large costs. The oft-bemoaned compliance costs for market participants may be alleviated if reporting requirements can be harmonized and data collection processes can be standardized.
Keywords: C82; G20; L14; 330; network analysis; interconnectedness; financial stability; stress-testing